Scrutinizing the Relationship between Subjective Anomalous Experiences and Psychotic Symptoms - Escolà-Gascón, Álex; Rusiñol Estragues, Jordi (Journal of Scientific Exploration, 2022)
Abstract This research was exploratory and its main objective was to analyze whether anomalous experiences related to parapsychology had similar statistical behavior to psychotic-like experiences (e.g., hallucinations). If psi phenomena have a different ontology from psychotic-like experiences, then they should have a different statistical representation and measurement. In this hypothetical scenario, there would be empirical-statistical grounds for discriminating between psychotic perceptual distortions and anomalous experiences without clinical origin. Different clinical variables common in psychotic disorders were measured in 562 participants. Psychotic-like experiences (as hallucinations) and anomalous experiences (as experiences outside the framework of psychosis) were also quantified. Several forward stepwise multiple regression models and techniques based on Exploratory Factor Analysis were used. The EFA extracted 2 factors; the first grouped the variables that measured anomalous phenomena from the continuum of psychosis model and the second gathered the variables that measured them as anomalous perceptions without scientific explanation. Both EFAs explained more than 70% of the variance. Only 3 clinical variables were necessary to predict 58.8% of psychotic –like experiences assessed from the psychopathological model. Up to 6 indicators were necessary to predict 54.5% of the unexplained anomalous experiences. There are empirical-statistical indicators in the used sample that enable the differentiation of the anomalous phenomena in the two prominent models. The variables that characterize the psychotic phenotype predict more successfully psychotic-like experiences than anomalous experiences. It is discussed whether the factors extracted in the EFA represent psychological constructs with different etiologies or if both dimensions come from the same underlying construct. Keywords: Anomalous Experiences; Schizotypy; Psychotic-like experiences; Paranormal Beliefs; Psi Phenomena.